A Study of Post-1980s Employees’ Work Motivation in Beijing - ZHU, S (2013)
As the post-1980s were becoming the main workforce in China’s economy, effectively motivate those young workers to be more creative and productive is an issues for all the managers. This paper is to investigate post-1980s employees, according to understand their personalities, living background, and social influences to dig out their real needs in work.